2006
DOI: 10.1523/jneurosci.3446-06.2006
|View full text |Cite
|
Sign up to set email alerts
|

Preference for Immediate over Delayed Rewards Is Associated with Magnitude of Ventral Striatal Activity

Abstract: Discounting future outcomes as a function of their deferred availability underlies much of human decision making. Discounting, or preference for immediate over delayed rewards of larger value, is often associated with impulsivity and is a risk factor for addictive disorders such as pathological gambling, cigarette smoking, and drug and alcohol abuse. The ventral striatum (VS) is involved in mediating behavioral responses and physiological states associated with reward, and dysregulation of the VS contributes t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

52
372
5
4

Year Published

2011
2011
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 505 publications
(439 citation statements)
references
References 29 publications
52
372
5
4
Order By: Relevance
“…Using fMRI, McClure et al (2004) found that in intertemporal choice tasks, areas of the brain that are closely associated with emotions, such as the limbic area and the medial prefrontal cortex, become activated only in choices that involve immediate monetary outcomes (see also Hariri et al 2006). Similar results have been observed with nonmonetary rewards (McClure et al 2007).…”
Section: Emotional Areas Of the Brain Are Only Activated By Immediatementioning
confidence: 76%
“…Using fMRI, McClure et al (2004) found that in intertemporal choice tasks, areas of the brain that are closely associated with emotions, such as the limbic area and the medial prefrontal cortex, become activated only in choices that involve immediate monetary outcomes (see also Hariri et al 2006). Similar results have been observed with nonmonetary rewards (McClure et al 2007).…”
Section: Emotional Areas Of the Brain Are Only Activated By Immediatementioning
confidence: 76%
“…This analysis localizes brain areas associated with emotional responsivity [7,24] and cognitive control [5,8], respectively. To perform this analysis, we combined both subject groups and conducted a voxel-wise, event related GLM analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Neurally, these process are linked to brain reward areas (including the ventral striatum, VStr, and ventromedial prefrontal cortex, VMPFC) and regions associated with executive functions (dorsolateral prefrontal cortex, DLPFC, and posterior parietal cortex, PPC), respectively [4 -6]. Individual differences in either reward-or executive control-related brain responses both predict rates of delay discounting [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…In public economics and political science, survey data are used to establish the dollar value of goods that are not traded in markets (such as clean air or the prevention of oil spills), and to poll likely voters before an election (Crespi, 1989;Diamond and Hausman, 1994;Carson et al, 1996;Mortimer and Segal, 2008). Hypothetical choices are also necessary in some types of psychology and neuroscience experiments in which measuring real choices is impractical or unethical, especially in the domain of distressing moral choices (Greene et al, 2001(Greene et al, , 2004Kühberger et al, 2002;Hariri et al, 2006;Monterosso et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In public economics and political science, survey data are used to establish the dollar value of goods that are not traded in markets (such as clean air or the prevention of oil spills), and to poll likely voters before an election (Crespi, 1989;Diamond and Hausman, 1994;Carson et al, 1996;Mortimer and Segal, 2008). Hypothetical choices are also necessary in some types of psychology and neuroscience experiments in which measuring real choices is impractical or unethical, especially in the domain of distressing moral choices (Greene et al, 2001(Greene et al, , 2004Kühberger et al, 2002;Hariri et al, 2006;Monterosso et al, 2007).The reliance on hypothetical choice data presumes either that hypothetical choices are a good and legitimate way to forecast real choices, or that there is some knowable relationship between the two types of choices, such that the hypothetical data can be adjusted to forecast real choice data accurately.Abbreviations: WTP, willingness-to-pay; CS, consumer surplus.However, many studies in behavioral economics have shown a substantial, systematic gap: typically, hypothetical valuations are greater than real valuations (Cummings et al, 1995;Johannesson et al, 1998;List and Gallet, 2001;Ariely and Wertenbroch, 2002;Little and Berrens, 2004;Murphy et al, 2005;Blumenschein et al, 2007;Tanner and Carlson, 2009). To remedy this typical upward "Yes" bias, in marketing research conjoint analysis using hypothetical preference data has been extended and improved through hybrid incentive-aligned methods in which an inferred choice will be implemented for real (Ding et al, 2005;Ding, 2007;Dong et al, 2010).…”
mentioning
confidence: 99%